THE INFLUENCE OF COLOR ON CONSUMER'S AFFECTIVE SIDE IN COMMERCIAL SPACE: A LITERATURE REVIEW APPROACH - I Putu Udiyana Wasista; Ni Luh Kadek Resi Kerdiati; Putu Ari Darmastuti (Yayasan Sinergi Widya Nusantara, 2022)
Purpose: This study aims to look at strategies for arousing consumers' affective side. The affective side studied is the desire to enter the room, the desire to shop, and the mood in a commercial space. Research methods: This study uses the library study method. This method uses literature as a source of research answers. The literature obtained will be categorized and analyzed to find valid answers. Findings: We need the right strategy in combining colors to form a space atmosphere that invites and arouses consumer shopping interest. Colors with a combination of blue or green-yellow are suitable for entrances, while cool colors are good for use in spaces. Cool colors will help influence shopping decisions and consumer moods. This combination is crucial in maximizing profits in commercial ventures. Implications: The role of color in a commercial space is significant. Designers must be able to choose colors wisely and flexibly. This choice is because each color has a different role and function in evoking the affective side of consumers.